DARI MINAT DAN MOTIVASI KE PRESTASI: STUDI KORELASIONAL SEPAK TAKRAW DI SMA NEGERI 1 MONTONG GADING - Intan Kusuma Wardani (Journal Sport Science, Health and Tourism of Mandalika (Jontak) e-ISSN 2722-3116, 2026)
This study aimed to determine students' interest and motivation in sepak takraw and to examine their relationship with perceived sepak takraw achievement at SMA Negeri 1 Montong Gading. The term achievement in this study refers to students' self-reported achievement orientation and perceived achievement scores measured through a validated questionnaire, not official competition records or objective skill-test results. The study used a quantitative descriptive-correlational survey with a cross-sectional design. The sample comprised 59 students from two classes selected through cluster sampling. Data were analyzed using descriptive statistics, residual normality testing, Pearson correlation, and multiple correlation using SPSS 29. The findings showed that students' interest was in the moderate category (63.15%), motivation was also in the moderate category (60.33%), whereas perceived achievement was in the low category (48.64%). Interest was positively and significantly related to perceived achievement (r = 0.416; p = 0.001), and motivation was also positively and significantly related to perceived achievement (r = 0.589; p < 0.001). Interest and motivation were jointly related to perceived achievement (R = 0.598; R² = 0.357; F = 15.564; p < 0.001). Because the design was correlational, the findings should be interpreted as associative rather than causal. Keywords: interest, motivation, achievement, sepak takraw, students Penelitian ini bertujuan untuk mengetahui tingkat minat dan motivasi peserta didik terhadap sepak takraw serta menguji keterkaitannya dengan persepsi prestasi sepak takraw di SMA Negeri 1 Montong Gading. Istilah prestasi dalam penelitian ini dibatasi sebagai skor persepsi prestasi dan orientasi prestasi yang diukur melalui angket, bukan data prestasi faktual berupa hasil lomba atau tes keterampilan objektif. Penelitian menggunakan pendekatan kuantitatif dengan desain survei deskriptif-korelasional secara cross-sectional. Sampel berjumlah 59 peserta didik dari dua kelas yang dipilih menggunakan teknik cluster sampling. Hasil penelitian menunjukkan bahwa minat berada pada kategori sedang sebesar 63,15%, motivasi berada pada kategori sedang sebesar 60,33%, sedangkan persepsi prestasi berada pada kategori rendah sebesar 48,64%. Minat berhubungan positif dan signifikan dengan persepsi prestasi (r = 0,416; p = 0,001), sedangkan motivasi berhubungan positif dan signifikan dengan persepsi prestasi (r = 0,589; p < 0,001). Minat dan motivasi secara bersama-sama memiliki keterkaitan dengan persepsi prestasi (R = 0,598; R² = 0,357; F = 15,564; p < 0,001). Karena penelitian ini bersifat korelasional, temuan tidak ditafsirkan sebagai hubungan sebab-akibat. Kata kunci: minat, motivasi, prestasi, sepak takraw, peserta didik